Facile phyto-mediated synthesis of ternary CuO/Mn3O4/ZnO nanocomposite using Nigella Sativa seeds extract: characterization,antimicrobial, and biomedical evaluations - Shahira H. EL-Moslamy; Yousra A. El-Maradny; Mohamed H. El-Sayed; Mohamed A. El-Sakhawy; Esmail M. El-Fakharany (Scientific Reports)
Abstract The phyto-synthesis of ternary CuO/ Mn3O4/ZnO nanocomposite was achieved by the utilization of an eco-friendly, straightforward approach that involved the extract of Nigella sativa seeds. Our ternary nanocomposite appears to include equal amounts of CuO, Mn3O4, and ZnO based on the atomic percentages. The results indicate that a robust and thermally stable CuO/Mn3O4/ZnO nanocomposite was developed in stable nanosuspensions. The CuO/Mn3O4/ZnO nanocomposites showed antimicrobial capabilities against multidrug-resistant human pathogens. The highest biofilm reduction in viable planktonic populations of all human pathogens investigated was significantly reduced by the CuO/Mn3O4/ZnO ternary nanocomposites with a value of 18.5 µg/mL. The unique, enhanced, and triple-combined properties enabled the nanocomposite to have strong antimicrobial ability. The CuO/Mn3O4/ZnO nanocomposite exhibited strong anticancer activity against A549, MDA, HCT-116, and HepG2 cells, with selectivity index values ​​ranging from 24.72 to 41.96. The CuO/Mn3O4/ZnO nanocomposite appeared to induce selective dose-dependent nuclear condensation and cell shrinkage in the treated cancer cells, significantly inducing the apoptosis mechanism to combat cancer progression. The phytosynthetic CuO/Mn3O4/ZnO nanocomposite appears to induce selective dose-dependent nuclear condensation and cell shrinkage in treated cancer cells, significantly triggering apoptotic mechanisms to combat cancer progression. This apoptotic pathway was confirmed by the strong affinity of CuO/Mn3O4/ZnO nanocomposites for ErbBs and VEGF with potent antioxidant activity to scavenge ABTS and DPPH radicals at EC50 values ​​of 236.6 µg/mL and 134.8 µg/mL, respectively.